MRI-compatible positioning device for guiding a focused ultrasound system for transrectal treatment of prostate cancer - Yiallouras, Christos; Mylonas, Nicos; Damianou, Christakis A. (My University, 2014)
Background   : High-intensity focused ultrasound (HIFU) is a promising treatment method for many common cancers, including prostate cancer. Magnetic resonance image (MRI) guidance of HIFU permits targeting and monitoring of therapy. A prototype MRI-compatible positioning device that navigates a HIFU transducer was designed, fabricated and tested. Materials and methods   : The positioning device has two PC-controlled and one manually driven stage that allow endorectal access to the prostate. The positioning device was constructed using a 3-D rapid prototype manufacturing device. Software was developed that controls the motion of the positioning device and enables activation of a HIFU transducer. In vitro testing of the system was performed in a 1.5T MRI scanner using ex vivo turkey tissue. Optical encoders were employed to enhance the accuracy of this positioning device. Result   : The positioning device was successfully tested for MRI compatibility. The movement error of the positioning device is approximately 20 μm. The robot has the ability to accurately move the transducer for creation of discrete and overlapping lesions. Conclusion   : An MRI-compatible HIFU positioning system was developed that has the ability to create thermal lesions with MRI guidance for endorectal treatment of prostate cancer.
Keywords: MRI; Prostate; Ultrasound